2007
DOI: 10.1093/jac/dkm019
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity against anaerobes of retapamulin, a new topical antibiotic for treatment of skin infections

Abstract: At

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 18 publications
2
18
0
1
Order By: Relevance
“…It has a low potential for organisms to develop resistance and has not shown cross-resistance to other antimicrobial classes. Retapamulin has been shown to be similar in efficacy to topical fusidic acid and to oral cephalexin for treating impetigo or infected traumatic lesions [40][41][42], but there are no data on use of this agent for chronic wounds.…”
Section: What Types Of Topical Antimicrobials Are Available?mentioning
confidence: 99%
“…It has a low potential for organisms to develop resistance and has not shown cross-resistance to other antimicrobial classes. Retapamulin has been shown to be similar in efficacy to topical fusidic acid and to oral cephalexin for treating impetigo or infected traumatic lesions [40][41][42], but there are no data on use of this agent for chronic wounds.…”
Section: What Types Of Topical Antimicrobials Are Available?mentioning
confidence: 99%
“…A novel semisynthetic pleuromutilin, retapamulin {mutilin 14-(exo-8-methyl-8-azabicyclo [3.2.1]oct-3-yl-sulfanyl)-acetate}, is active against Staphylococcus aureus and Streptococcus pyogenes (39,47) and is the first pleuromutilin derivative which has been formulated as a topical antibacterial agent for treating human skin infections (14,38,41). In 2007, the Food and Drug Administration and the European Commission approved a new topical retapamulin ointment for the treatment of impetigo and infected small lacerations, abrasions, or sutured wounds.…”
mentioning
confidence: 99%
“…Retapamulin demonstrated favorable in vitro activity against anaerobes, including Propionibacterium species associated with acnes vulgaris, Fusobacterium species, and other anaerobic Gram-positive cocci, 14,17,24 and respiratory tract pathogens, including Haemophilus infl uenzae, Streptococcus pneumoniae, and Moraxella catarrhalis. 16 The in vitro activities of retapamulin against common pathogens associated with uncomplicated SSSIs reported in published studies correspond well with those found in the global surveillance program.…”
Section: In Vitro Activity Of Retapamulin: Published Studiesmentioning
confidence: 99%
“…13 A recent addition to available topical antibiotics is retapamulin, a novel semisynthetic pleuromutilin antibiotic that has a unique mode of action and potent in vitro activity against a wide range of pathogens, particularly Gram-positive cocci. [14][15][16][17] An ointment formulation of 1% retapamulin received regulatory approval from the US Food and Drug Administration for the treatment of impetigo and from the European Medicines Agency in 2007 for the short-term treatment of the following superfi cial skin infections: impetigo and infected small lacerations, abrasions, and sutured wounds. Retapamulin is the fi rst new prescription topical antibiotic in more than 20 years.…”
mentioning
confidence: 99%